Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar Siswa Kelas XI IPA Di SMA Negeri 2 Pasangkayu Pada Pokok Bahasan Bentuk Molekul - Lestari, Lestari; Tangkas, I Made; Sabang, Sri Mulyani (Jurnal Akademika Kimia, 2014)
The basic principle in the learning activities is student-centered learning. This requires a learning model that empowers students to be more actively involved in the learning process at school one cooperative learning model Two Stay Two Stray (TSTS). This study aims to determine the effect of cooperative learning model TSTS to see a difference in student learning outcomes between cooperative learning model TSTS and conventional learning on the subject of molecular geometry. The study population was all students class XI Science SMAN 2 Pasangkayu Academic Year 2013/2014. The study sample consisted of two class, namely class XI Science 2 as many as 25 people as the experimental class and class XI Science 1 by 27 people as the control classes determined by purposive sampling. Data collection was conducted using test instruments which consist of 20 items. Testing research data used t-test statistical analysis of the two parties with the prerequisite test that tests for normality and homogeneity tests. Average score of student learning outcomes using cooperative learning model TSTS is 74.06 while the average score of student learning outcomes that follow conventional learning is 66.5. Based on statistical analysis by t-test hypotheses two parties obtained tcount = 2.83 and this is in the region of rejection of Ho, namely -2.00 and 2.00. These results indicate that there are differences in student learning outcomes given cooperative learning model TSTS with conventional.